PEMANFAATAN FASILITAS TEMPAT PENDARATAN IKAN - Muhammad Agam Thahir; Muhammad Arif Nasution (Universitas Teuku Umar, 2017)
This study was carried out at Merbau district fishing port. Purpose of this study is to know type, capacity and optimalization of utilizing level on fishing port’s facilities by survey method. The survey result showed, the available facilities at Merbau district fishing port is jety, manuver area, heigbour, dolphin, fish processing warehouse, base camp and fishing gear warehouse, Capacity and optimalization of utilizing level were 13.37 and 7.48% respectively. Meanwhile, the water depth of manuver area was 0.7 m and optimalization of utilizing level was 140%. Capacity of heigbour was 84,03 kg, with optimalization of utilizing level was 11.9%.